Video assisted thoracic surgery. Experiences in Dr. Gustavo Aldereguia Lima hospital. - Arístides Sánchez Sánchez; Lidia Torres Aja; Rubén Mena Guerra; Francisco Cabarroca Castillo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Video assisted thoracic surgery is an intervention which advantages should be reaffirmed through studies aimed to characterize and describe it, based on real experiences. Objective: To verify the efficacy of this kind of surgery in the department of minimal access surgery in the university hospital Dr. Gustavo Aldereguia Lima. Methods: Descriptive, retrospective study of 135 patients operated through video assisted thoracic surgery in the university hospital in Cienfuegos during a period of seven years (1998-2005). The analyzed variables were: disease that determined the intervention, goals, of the intervention, complications and post-operatory period. Results: The most frequent causes of intervention were pneumothorax, pulmonary tumors, pleural effusion and empyema. There was high accordance between pre and pos operatory diagnosis. There was a prevalence of therapeutic surgeries (55 %), over diagnostic surgeries. The pos-operatory period in the Surgery Department was less than seven days in most of the cases. Conclusion: The study's results show that the use of this technique has a positive impact on the economic and social indicators of the province.